Pushing the limits of V2: new syntactic options in a Danish urban dialect - Zachariassen, Ditte (Scandinavian Studies in Language, 2023)
Studies of urban dialects in the Germanic languages show a development where the otherwise strict V2 syntax rules are supplemented with V3 syntax in specific syntactic and social contexts. Based on recordings of naturally occurring interaction in multilingual areas of Aarhus, Denmark, this paper adds to existing research with an interactional collection analysis of actions supporting V3. It describes six structural subtypes of V3 characterised by different adverbial and object material in first position and shows how the subtypes are connected to three interactional resources used in organising storytelling, claiming epistemic authority and reframing referents or discourse. V3 is often used when contrasting one type of information with another. It does not result in a different semantic meaning, rather it existing possible meanings that could also be emphasised by extra wording or multiple sentences. In the discussion, I argue that the extra syntactic options allow speakers to say more with fewer words by pushing the limits of the rather strict V2 syntax of Standard Danish.